Day6’s congratulations and letting go song lyrics analysis: A pragmatics study - MegasariJayanti; MarshandaAulia Ridha; PrasetyaRuth Ika (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
This research is a pragmatic study that aims to find and describe the function of implicatures, and types of presuppositions contained in DAY6’s Song “Congratulations” and “Letting Go” lyrics. The implicatures study is used to find the implied meanings that are contained in a song while the presuppositions study is used to find the type of presuppositions of the song. Both of these songs were written in Korean, which in this study were translated into Indonesian to find out the meaning contained in the lyrics. This research used a descriptive method with listening and note-taking techniques to collect the data. The step that the writer took was listening to the song while reading the lyrics, checking the translated version of the songs that were written in English to understand the meaning, and doing the analysis periodically. The analysis results were presented using an informal method. The results showed that there were five implicature functions found in the Congratulations song. While, in the Letting Go, there was one. The implicature functions that have been found were sarcasm and parable functions. There were four types of presuppositions found in each song: lexical presupposition, structural presupposition, counterfactual presupposition, and factive presupposition.